On Combustion of Diesel Fuel Drops at LPG Fuelling by Diesel Gas Method. (2016) - Cernat, Alexandru; Pana, Constantin; Negurescu, Niculae; Nutu, Cristian
Abstract: The Liquid Petroleum Gas can be use at diesel engine with significant reductions in nitrous oxides and smoke emissions and affects the in-cylinder mixture forming and combustion process. The paper presents the results of a thermodynamic model developed for vaporization and combustion processes simulation for an automotive diesel engine fuelled with LPG by diesel gas method. The mass flow of vaporized substance at the particle area, drops combustion time and flame position are determinate, showing a significant influence of LPG cycle dose on their characteristic parameters. The drops combustion duration decreases for dual fuelling and the flame radius increases.